1997
DOI: 10.1007/s004410050913
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and morphology of inhibitory innervation in crayfish ( Procambarus clarkii ) limb and abdominal muscles

Abstract: The general morphology and distribution of inhibitory nerve terminals in representative limb and abdominal muscles of the crayfish (Procambarus clarkii) were studied by using a polyclonal antiserum against conjugated gamma-aminobutyric acid. A double-labelling procedure with gamma-aminobutyric acid and synaptotagmin antisera was employed to study the relationship between inhibitory and excitatory innervation. The neuromuscular junctions were visualized with confocal scanning laser microscopy. Two morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
2
9
1
Order By: Relevance
“…These findings are in agreement with the observations of Msghina and Atwood (1997), who compared the phasic and tonic inhibitory innervation in disparate limb and abdominal muscles. Our quantitative findings in a unified functional system, that of the deep and superficial abdominal extensor muscles, supports the conclusion that structural differences relate specifically to the functional class (phasic vs. tonic) of muscle that the axons innervate.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with the observations of Msghina and Atwood (1997), who compared the phasic and tonic inhibitory innervation in disparate limb and abdominal muscles. Our quantitative findings in a unified functional system, that of the deep and superficial abdominal extensor muscles, supports the conclusion that structural differences relate specifically to the functional class (phasic vs. tonic) of muscle that the axons innervate.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, we report here that a majority of the lobster neuromuscular synapses have no associated dense bars, and that these lobster synapses have many fewer dense bars, overall, than have been reported for synapses on the crayfish dactyl opener muscle. In addition, whereas previous studies have reported that excitatory and inhibitory innervation sites on the crayfish dactyl opener muscle are co-localized (Govind et al 1994(Govind et al , 1995aCooper et al 1996a;Msghina and Atwood 1997), we have observed relatively large (~20 μm) regions in which inhibitory terminals are present, but excitatory terminals are absent, in lobster dactyl opener. These morphological differences are likely to have important implications for the interpretation of physiological data recorded from neuromuscular synapses in the dactyl opener of lobster.…”
Section: Introductioncontrasting
confidence: 73%
“…2B and D). This is similar to synaptotagmin labeling in crayfish motor neurons, where the protein is distributed in nerve terminals of excitatory and inhibitory motor neurons (Cooper et al, 1995;Msghina and Atwood, 1997). The Ha-CalpM staining pattern was not correlated with claw type (cutter vs. crusher) or with stage in the molt cycle (premolt, postmolt, or intermolt).…”
Section: Discussionmentioning
confidence: 55%